Organic Synthesis in Boric Acid: A Study on the Scope and Developments: Exploring the Versatility of Boric Acid in Organic Synthesis (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Recent years have seen an increase in the use of boric acid [H3BO3]. Here, the most recent developments in boric acid catalysed transformations, such as esterification and transesterification are summarised, as well as the addition of azide and thiazide and the aza- and thia-Michael additions, condensation and the Friedel-Crafts and Tishenko reactions, as well as halogenations, ipso substitutions, decarboxylations, reactions of protection and deprotection, amidation and A number of biologically relevant chemical molecules have been synthesised using Boric acid as a benign, commercially available, and inexpensive catalyst in the recent decade.